2020
DOI: 10.3390/molecules25102438
|View full text |Cite
|
Sign up to set email alerts
|

3D Micro/Nanopatterning of a Vinylferrocene Copolymer

Abstract: In nanoimprint lithography (NIL), a pattern is created by mechanical deformation of an imprint resist via embossing with a stamp, where the adhesion behavior during the filling of the imprint stamp and its subsequent detachment may impose some practical challenges. Here we explored thermal and reverse NIL patterning of polyvinylferrocene and vinylferrocene-methyl methacrylate copolymers to prepare complex non-spherical objects and patterns. While neat polyvinylferrocene was found to be unsuitable for NIL, fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Ferrocene, an extremely useful and unique building block, has remained at the centre of attraction for several decades now. 1,2 Being an essential component in organometallic polymers, [3][4][5][6][7][8][9][10] redox-tunable substances, 6,[11][12][13] organometallic drugs, 14,15 and functional materials, 9,[16][17][18][19][20] ferrocene has played a vital role in homogenous catalysis. [21][22][23][24][25] The principle reasons for its popularity in homogenous catalysis lie in the easy syntheses of its P-functionalized derivatives (such as dppf ) and a flexible backbone, 26,27 which provides an opportunity to stabilize various metal centers by attaining facile geometric changes.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrocene, an extremely useful and unique building block, has remained at the centre of attraction for several decades now. 1,2 Being an essential component in organometallic polymers, [3][4][5][6][7][8][9][10] redox-tunable substances, 6,[11][12][13] organometallic drugs, 14,15 and functional materials, 9,[16][17][18][19][20] ferrocene has played a vital role in homogenous catalysis. [21][22][23][24][25] The principle reasons for its popularity in homogenous catalysis lie in the easy syntheses of its P-functionalized derivatives (such as dppf ) and a flexible backbone, 26,27 which provides an opportunity to stabilize various metal centers by attaining facile geometric changes.…”
Section: Introductionmentioning
confidence: 99%
“…For several decades, manufacturing methods have been further developed to fabricate micro- and nanostructures cost- and time-efficiently, while maintaining high precision in shape and in high throughput [ 1 , 2 , 3 ]. Ruprecht et al demonstrated a high aspect ratio microstructuring using LIGA process (German acronym for lithography, electroplating, and molding) already in 1993 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%